APPROXIMATIONS OF STOCHASTIC INTEGRALS OF THE POISSON PROCESS (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this article the asymptotic behavior of the finite sums of the elements depending on approximations, being linear combinations of approximations by I to and Stratonovich, is investigated. The outcomes of the present work are generalizations of the corresponding theorems from